Effects of functional resistance training on muscle strength and musculoskeletal discomfort - Cassemiro,Bruna Montechieze (Pontifícia Universidade Católica do Paraná, 2017)
Abstract Introduction: Functional resistance training (FRT) is becoming increasingly popular to improve physical fitness of practitioners, however, yet there are gaps in knowledge about effectiveness of FRT in relation conventional resistance training (CRT) in several ambits, as musculoskeletal complaints. Objective: Compare the effect of FRT and CRT in the musculoskeletal discomfort and magnitude of gain in muscle strength in healthy women. Methods: 52 women was divided into three groups, FRT (n = 15; 22 ± 2.35 years): functional resistance training; CRT (n = 14; 22.5 ± 1.78 years): conventional resistance training and CG (n = 13; 20.6 ± 1.10 years): no type of intervention. The training was periodized in 30 sessions over 12 weeks with 3 sessions per week. For the muscle strength variable used the 1RM test and for the musculoskeletal discomfort variable, the Nordic Musculoskeletal Questionnaire (NMQ). Regarding the statistical analysis, all results took into consideration a 5% level of significance. Results: Considerable gain in muscle strength was observed for all exercises in both training groups. In addition, there was a tendency in CRT to relate a more musculoskeletal discomfort; presented 27.3% more complaints compared FRT in the MNQ. Conclusion: The FRT was as effective as the CRT for improving muscle strength, furthermore, there was a tendency for FRT to cause less musculoskeletal discomfort.